Piloting a New Virtue Education Curriculum for 5–15-Year-Old Students: What are the Most Challenging Issues in Its Delivery? - Surikova, Svetlana; Sidorova, Anna (Pedagogika, 2023)
The article analyses Latvian teachers’ opinions regarding the feasibility of a virtue education curriculum for students aged 5–15 years, which they piloted in spring 2021, and identifies the challenges faced when implementing the virtue education curriculum during the COVID-19 pandemic. The findings showed that the curriculum could be delivered successfully in both modalities – face-to-face and online – since the teachers’ approaches were creative and transformative in addressing all the challenges identified.